Dr. Christian Stallworth — Deep Plane Facelift — San Antonio - Stallworth, Christian (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Christian Stallworth, practicing in San Antonio, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003156; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; san antonio